Nephrotic syndrome leading to recurrent pulmonary embolism: A report of two cases: Recurrent pulmonary embolism in nephrotic syndrome - Agarwal, Mehul; Sharma, Krishna Kumar; Bharti, Neha; Deokar, Kunal (Acta Biomedica Atenei Parmensis, 2022)
.